«Myths of Reality» and «Myths of Fantasy» in Los terribles amores de Agliberto y Celedonia (1931) by Mauricio Bacarisse - Coste, Gregory (Amaltea. Revista de Mitocrítica, 2018)
In this article I propose to analyze the theoretical and structural opposition that Mauricio Bacarisse vindicates and illustrates in his novel Los terribles amores de Agliberto y Celedonia (1931). While the “myths of fantasy” restrict the freedom of individuals and serve to justify a conformist society and a mutilated identity, the “myths of reality”, aroused by literary creation, generate a foundational mythology capable of taking into account all facets of the reality and the individual against the narrowness of a falsifying imagination that impoverishes or simplifies them.